2008
DOI: 10.5688/aj720485
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Awards at US Colleges and Schools of Pharmacy

Abstract: Objectives. To determine recognition given for outstanding teaching, service, and scholarship at US colleges and schools of pharmacy, the types of awards given, and the process used to select the recipients. Methods. A self-administered questionnaire was made available online in 2006 to deans at 89 colleges and schools of pharmacy. Results. Sixty-four usable responses (72%) were obtained. An award to acknowledge teaching excellence was most commonly reported (92%), followed by an award for adjunct/volunteer fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Indeed, Kalis and Kirschenbaum concluded that teaching awards do in fact enhance retention and morale. 4 Those outcomes, however, may not be automatic, at least not for all disciplines. Aucott and colleagues found that awards for teaching excellence do not translate necessarily into faculty retention.…”
Section: Teaching Awardsmentioning
confidence: 99%
“…Indeed, Kalis and Kirschenbaum concluded that teaching awards do in fact enhance retention and morale. 4 Those outcomes, however, may not be automatic, at least not for all disciplines. Aucott and colleagues found that awards for teaching excellence do not translate necessarily into faculty retention.…”
Section: Teaching Awardsmentioning
confidence: 99%
“…51 Various categories of preceptor recognition exist (eg, new preceptor of the year, IPPE preceptor of the year, APPE preceptor of the year) as well as differing mechanisms for selecting preceptor awards (i.e., student pharmacist vote, school/college committee vote following nominations, administrative decision, or course evaluation surveys). 48 National pharmacy practice organizations also recognize the value of pharmacy preceptors and examples of such recognition programs are listed in Table 4.…”
Section: Recognition Of Preceptor Teaching Excellencementioning
confidence: 99%
“…30 In a survey of preceptor awards provided by schools/colleges, 79% of the respondents indicated providing recognition for preceptors/volunteer faculty members. 48 Recognitions included a plaque or certificate, recognition at a ceremony/ luncheon, monetary award, and/or travel funds for a professional conference. 48 Other forms of preceptor recognition have included authorship in preceptor/experiential education newsletters and recognition in national communications.…”
Section: Recognition Of Preceptor Teaching Excellencementioning
confidence: 99%
See 2 more Smart Citations